A Clinical Decision Support System as a Tool to Improve the Accuracy of Nursing Diagnoses - Wikan Purwihantoro Sudarmaji; Sholihin Sholihin; Roby Aji Permana; Agustina Soares; Yanuar Aga Nugraha (Universitas Airlangga, 2019)
Introduction: Nursing diagnosis is an important part of the nursing process and it influences the quality of nursing care. Accuracy in establishing nursing diagnoses is one of the factors that determines the accuracy of the nursing intervention program and the speed of healing of the patients. The Clinical Decision Support System is an information system built to assist health workers in making clinical decisions including the enforcement of nursing diagnoses. Through this systematic review, the author wants to explain the clinical decision support system as a tool to increase the accuracy of the enforcement of nursing diagnoses.Methods: The search for journals using the PICOT framework was conducted in the Scopus, Proquest, PubMed and Cinahl databases with a 10-year publication time limit (2008 - 2018). There were 8 international journals reviewed in full.Results: Generally the journals reviewed stated that the use of the Clinical Decision Support System in establishing nursing diagnoses has been shown to improve the accuracy of nursing diagnoses.Conclusion: This systematic review concludes that the use of clinical decision support systems can help nurses or nursing students in establishing accurate nursing diagnoses.